Expanding the phenotypic spectrum of Mendelian connective tissue disorders to include prominent kidney phenotypes. Issue 12 (6th August 2021) - Strong, Alanna; Skraban, Cara; Meyers, Kevin; Amaral, Sandra; Furth, Susan; Drant, Stacey; Hsiao, Wendy; Galea, Lauren; Gold, Jessica; Gold, Nina B.; Leonard, Jacqueline; Lopez, Sonya; et al.
Abstract: Heritable connective tissue disorders are a group of diseases, each rare, characterized by various combinations of skin, joint, musculoskeletal, organ, and vascular involvement. Although kidney abnormalities have been reported in some connective tissue disorders, they are rarely a presenting feature. Here we present three patients with prominent kidney phenotypes who were found by whole exome sequencing to have variants in established connective tissue genes associated with Loeys‐Dietz syndrome and congenital contractural arachnodactyly. These cases highlight the importance of considering connective tissue disease in children presenting with structural kidney disease and also serves to expand the phenotype of Loeys‐Dietz syndrome and possibly congenital contractural arachnodactyly to include cystic kidney disease and cystic kidney dysplasia, respectively.